Business Process Reengineering of Motor Vehicle Insurance Claims Using the Business Process Reengineering Method - Satrya Hidayat; Amrul Hidayat; Achmad Zidane Fatih Ramadhan; Keysha Azzahra Putri; Tasyaufy Isma Nur Aulia; Raulia Riski (Universitas Negeri Surabaya, 2026)
In the current era of digital transformation, motor vehicle insurance claim services can be rendered significantly more effective. However, PT Asuransi Umum Bumiputera Muda 1967 (BUMIDA) encounters challenges with manual vehicle surveys, which lead to prolonged queues in claim services. To address this issue, enhancing the business processes associated with the provision of motor vehicle insurance claim services is imperative. The objective of this research is to analyze the motor vehicle insurance claim process utilizing the Business Process Reengineering (BPR) method and to propose an optimized process. The methodology employed in this study encompasses analyzing the current (As-Is) business process, formulating the problem, designing the proposed (To-Be) business process, and ultimately executing a process simulation using BPMN 2.0 within the Visual Paradigm application. The primary finding indicates that the implementation of digital surveys integrated with video calling technology can significantly enhance the business process and eliminate bottlenecks within the vehicle surveying procedure. The newly proposed process and subsequent improvements are anticipated to substantially increase the efficiency of the motor vehicle insurance claim services provided by the company.